The overweight female body in Malaysian slimming advertisements: problem and solution - Zuraidah, Mohd Don; Lau, Emily Kui Ling (Taylor & Francis, 2018)
This study analyses image and text to investigate the way slimming advertising exploits women’s fear of being overweight to the extent that they feel obliged to do something about their own bodies. We show how Malaysian slimming advertisements construct certain types of female body which reinforce cultural stereotypes, namely the overweight body that exceeds culturally acceptable limits of desirable body size, and the desirable and attainable slim body with no excess fat. Three sample advertisements were selected from a Malaysian English newspaper and analysed using Jewitt and Oyama’s framework to identify the way images and text are used to give specific meanings relating to the female body. The images were examined in terms of representational, interactional and compositional meanings, and the analysis provides evidence of how the extremely overweight female body is pathologised, making it the focus of critical scrutiny. The advertisements use body images to illustrate the problem of being very overweight and the desirability of being slim, and the consumption of slimming services as a quick and easy solution to the problem.